The current account and monetary policy in the euro area - Tobias Schuler; Yiqiao Sun (European Central Bank (ECB), 2022)
We investigate the factors driving current account and monetary policy developments in the euro area. We estimate an open-economy structural vector autoregression (VAR) model with zero and sign restrictions derived from a multi-country dynamic stochastic general equilibrium (DSGE) model to identify relevant shocks and analyse their impact on the current account and interest rate. Examining the VAR impulse responses for Germany, Italy and Spain we find that investment shocks and preference shocks drive the current account and interest rates in the opposite directions. By contrast, external demand shocks and productivity shocks cause both the current account balance and interest rate to move in the same direction. We also provide evidence for spillovers to the euro area from US preference shocks and US interest rate policy shocks.
Keywords: E32; F32; F45; 330; current account; monetary policy; macroeconomic shocks